A case study - Nietes, Thelma (Animo Repository, 1978)
This is a case study of a recommendation of a high school principal for a non-renewal of a contract of a Spanish teacher.Mt. Carmel High School is a co-educational, diocesan school established to serve the needs of Sierra Nova community. When Father Romeo Niego took his office as parish priest and at the same time Director of Mt. Carmel High, he was less inclined to education, so he entirely left the management of the school to his lay principal, Nico Amor. Amor was the oldest and had the most number of years of service in the school. Being on his retirement stage, he did not care much about his administrative and supervisory work, so much so that disciplinary problems and lack of teacher's preparation especially among the old timers were at stake. After considering reports from concerned parents and following an investigation on the matter, the Bishop sent Magno Vicente, young faculty member, to take a course in Educational Administration. Upon completion of his studies, Vicente succeeded Nico Amor as the new principal. Vicente carried on his new tasks, which among others included conducting a series of class observations.The observations had brought about a heated discussion between the principal and the Spanish teacher, Santa Marcalinas. The Spanish teacher at Mt. Carmel had been observed a number of times by the principal. Mr. Vicente, during these instances of class observations, observed Marcalinas as having difficulty. It seemed to Vicente that in Marcalinas' class a motivation problem existed. The students were noisy and they showed little respect for their Spanish teacher. Mr. Vicente held a post visitation conference with Marcalinas. The principal found her to be irritable and indifferent to suggestions, and even difficult to engage in conversation. In the class observation that followed, there was little noticeable improvement in the class situation.Consequently, Vicente completed the teacher evaluation form, noting Marcalinas' inadequacies and concluding with a recommendation that her contract not be renewed. During the conference with the Spanish teacher the next day prior to the submission of the recommendation, Marcalinas accused the principal of failure to provide her with adequate supervision and threatened to take the issue to court, if the school does not rehire her.The following questions raised in the instant case are: 1) What would be the response to the accusation and the threat? 2) What are the teacher characteristics and behavior associated with teacher effectiveness? 3) What the principal's responsibilities toward a teacher to improve on effectiveness? 4) What factors led to the conclusion drawn by Mr. Vicente based on classroom observations. What other conclusions could be drawn? 5) What are the other alternatives?